Tello, Julio C., Paracas— Primera parte. Lima, Empresa Gráfica T. Scheuch, S. A., 1959. 4h. (incl. front. col.), 307 p. (incl. xciii láms. col. y 45 en negro), mapa pl. fuera de texto - Tauro del Pino, Alberto (Revista Histórica, 1958)
Sin resumen.